Medicinal Plants in East Sumba that Potential as Natural Dyes for Ikat Weaving - Martini Ndamunamu; Irmanida Batubara; Leti Sundawati (Syarif Hidayatullah State Islamic University, 2019)
The revival of the natural dyes comes from an awareness of maintaining health and preserving the environment. Medicinal plants can be used as a source of the natural dyes. This study aimed to determine the medicinal plants in East Sumba Regency potentially exploited as a natural dye for ikat weaving. Plant data was obtained from Tana Tuku village and Mbatakapidu village in East Sumba Regency. A total 13 species of plants were extracted to dye cotton fabric and mordant by FeSO4 (ferrous sulphate), Al2(SO4)3 (alum) dan CaCO3 (lime). The intensity of color L*, a*, b* were analyzed by Kruskal Wallis test and Duncan post hoc test. The fastness of washing test analyzed by a gray color change scale and staining scale standard. The results showed that the ferrous sulphate mordant produced dark color and the alum mordant produced bright color. The intensity of red color was shown by Swietenia macropylla King and Leucaena leucocephala when it was mordanting by lime. The intensity of yellow color was shown by Woodfordia fruticosa (L.) Kurz with alum and Syzigium polyanthum with lime. The color change was not significant at 40 oC of washing shown by Tamarindus indica and Leucaena leucocephala mordanting by ferrous sulphate, Leucaena leucocephala, Bombax ceiba and Timonius timon mordanting by alum, Tamarindus indica, Leucaena leucocephala, Timonius timon mordanting with lime. All natural dyes did not stain the upholsteries.